Airborne SARS-CoV-2 Detection by ddPCR in Adequately Ventilated Hospital Corridors - Joan Truyols-Vives; Marta González-López; Antoni Colom-Fernández; Alexander Einschütz-López; Ernest Sala-Llinàs; Antonio Doménech-Sánchez; Herme García-Baldoví; Josep Mercader-Barceló (Toxics, 2025)
Indoors, the infection risk of diseases transmitted through the airborne route is estimated from indoor carbon dioxide (CO2) levels. However, the approaches to assess this risk do not account for the airborne concentration of pathogens, among other limitations. In this study, we analyzed the relationship between airborne SARS-CoV-2 levels and environmental parameters. Bioaerosols were sampled (n = 40) in hospital corridors of two wards differing in the COVID-19 severity of the admitted patients. SARS-CoV-2 levels were quantified using droplet digital PCR. SARS-CoV-2 was detected in 60% of the total air samples. The ward where the mildly ill patients were admitted had a higher occupancy, transit of people in the corridor, and CO2 levels, but there were no significant differences in SARS-CoV-2 detection between wards. The mean CO2 concentration in the positive samples was 569 ± 35.6 ppm. Considering all samples, the CO2 levels in the corridor were positively correlated with patient door openings but inversely correlated with SARS-CoV-2 levels. In conclusion, airborne SARS-CoV-2 can be detected indoors with optimal ventilation, and its levels do not scale with CO2 concentration in hospital corridors. Therefore, CO2 assessment should not be interpreted as a surrogate of airborne viral presence in all indoor spaces.